2016
DOI: 10.1007/s13187-016-1102-6
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Cervical Cancer Education Intervention for Latinas Delivered Through Interactive, Multimedia Kiosks

Abstract: US Latina women experience disproportionately high cervical cancer incidence and mortality rates. These health disparities are largely preventable with routine pap tests and human papillomavirus (HPV) screening. This study tested the efficacy of a cervical cancer education intervention to improve risk factor knowledge, attitudes, self-efficacy, and self-reported behavior related to cervical cancer screening among low-income Latinas who had not been screened in the past 2 years, compared to a usual care control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
36
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 45 publications
8
36
2
3
Order By: Relevance
“…This means that although the knowledge score signi cantly increased in both the control and test groups at all the stages following the intervention, the overall comparison of the two groups showed that this increase was signi cantly higher in the test group. This hints at the impact of the educational intervention on raising the knowledge score, which is consistent with the ndings of other studies [19,[21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This means that although the knowledge score signi cantly increased in both the control and test groups at all the stages following the intervention, the overall comparison of the two groups showed that this increase was signi cantly higher in the test group. This hints at the impact of the educational intervention on raising the knowledge score, which is consistent with the ndings of other studies [19,[21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 91%
“…Upon comparing the two groups, the mean attitude scores in the test group immediately after the intervention (adjusted for the pre-intervention attitude score), 4 weeks after the intervention (adjusted for the immediate post-intervention attitude score), and 12 weeks after the intervention (adjusted for the attitude score 4 weeks postintervention) were higher than the attitude scores in the control group at the same stages (8.61, 1.53 and 2.33, respectively) and statistically signi cant (P < 0.001). These results indicate the impact of the intervention on improving the attitude score, and are consistent with those of similar studies [21,22,24, 28] Roland et al [29] showed that the educational intervention had no impact on raising the participants' attitude score, a nding contrary to ours. This inconsistency may be attributed to the lack of dynamicity of the educational method, which used documented material at the beginning of the study, whereas, in our study, the educational material was presented in consecutive sessions where in the participants were in touch with the educator and there were Q & A sessions as well.…”
Section: Discussionsupporting
confidence: 90%
“…In a smaller study of Chinese Americans (n = 40), researchers found they were able to increase knowledge through a culturally tailored education intervention; however, their focus was only on breast cancer and along with the use of multimedia as their method of delivery their intervention may have had a different effect on participants (Wang et al 2008). Similar results were seen in an interactive intervention using a kiosk in the Latino population; however, knowledge in the Latino population was lower at baseline compared to our study population (Valdez et al 2018).…”
Section: Discussionsupporting
confidence: 59%
“…First, they would provide further evidence of the benefits of utilizing multimedia and family-based approaches in intervention development to enhance the effectiveness of health promotion interventions. Indeed, multimedia interventions were previously shown effective in enhancing the knowledge of ethnic minorities on cancer and improving their self-efficacy in undergoing cancer screening [32, 33]. Likewise, a systematic review also demonstrated the benefits of family-based interventions on improving the outcomes of diabetic patients [26].…”
Section: Discussionmentioning
confidence: 99%